N addition alters growth, non-structural carbohydrates, and C:N:P stoichiometry of Reaumuria soongorica seedlings in Northwest China - Xie, Tingting; Shan, Lishan; Zhang, Wanting (Scientific reports, 2022)
Reaumuria soongorica is an important biological barrier for ecological protection in the Gobi Desert in northwestern China, where soil nitrogen availability is low. N deposition has recently increased significantly in Gobi Desert, and the responses of R. soongorica to N enrichment may become a problem for ecological restoration and protection. However, little is known about the effects of N addition on the biomass, non-structural carbohydrates (NSC), and carbon:nitrogen:phosphorus (C:N:P) stoichiometry of R. soongorica in this region. Here, we examined changes in biomass, NSC and C:N:P ratios of different organs of R. soongorica seedlings in four N addition treatments: 0 (N 0 ), 4.6 (N 1 ), 9.2 (N 2 ), and 13.8 (N 3 ) g m −2 year −1 . N addition up to 9.2 g m −2 year −1 significantly increased the biomass of different organs, simultaneously increasing the belowground: aboveground ratio of R. soongorica seedlings. Root NSC concentrations significantly increased under all N addition treatments, but leaf and stem NSC concentrations only increased under the N 1 and N 2 addition treatments. Nitrogen addition enhanced the soluble sugar concentrations (SSC) of leaves and roots, and reduced starch concentrations (SC) of all organs. Stem and root N concentrations significantly increased under the N 2 and N 3 treatments, and leaf N concentrations only increased under the N 3 treatment, but N addition had no significant effect on plant C and P concentrations. Leaf and stem C:N ratios decreased significantly under the N 2 and N 3 treatments, but root C:N decreased significantly in all N addition treatments. The N 3 treatment significantly increased the N:P ratio of all organs. N addition significantly enhanced available N (AN), available P (AP) and total phosphorus (TP) in rhizosphere soil. Our results suggest that N addition alters the biomass, NSC, N concentrations, C:N and N:P ratios of all plant organs, but roots responded more strongly than stems or leaves to N addition, potentially allowing the plants to absorb more water from the arid soil in this region ensuring the survival of R. soongorica seedlings. Rhizosphere soil AP, AN and TP concentrations were important factors affecting the NSC concentrations and stoichiometric characteristics of R. soongorica .